Enhanced productivity of lipid extraction by urea stress conditions on marine microalgae Coelastrum sp. for improved biodiesel production - Bhuyar, Prakash; Sundararaju, Sathyavathi; Mohd Hasbi, Ab. Rahim; Gaanty Pragas, Maniam; Govindan, Natanamurugaraj (Elsevier, 2021)
Present investigation focused on marine microalgae strain Coelastrum sp. for enhanced biodiesel production. Microalgae grow when stressed and produce enhanced lipids despite urea being present. The dry cell weight, chlorophyll (a) content and total biomass yield increased productivity after the addition of urea in the nutrient medium. The chlorophyll (a) concentration and biomass yield obtained was 5.8839 μg/mL and 0.2357 ± 0.14 g. However, Coelastrum sp. obtained 41% of dry lipid under the absence of urea source than other microalgae species. The presence of some FAME components in the Coelastrum sp. provides scientific evidence for major constituent marine microalgae biodiesel. The GCMS revealed that major chemical constituents were hexadecanoic acid, Phthalic acid, di (3,4-dimethyl) ester, 5-(2-Aminopropyl)2-methylphenol and Phenethylamine, p, alpha-dimethyl (please add biodiesel yield or FAME %). The use of marine microalgae stressed by nitrogen source will beneficial to produce commercially viable biodiesel.